2020
DOI: 10.15611/pn.2020.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Means-End Chain theory: a critical review of literature

Abstract: This study provides the first critical and systematic investigation of the literature on Means-End Chain theory after the groundbreaking book "Understanding Consumer Decision Making: The Means-End Approach to Marketing and Advertising Strategy" by Olson and Reynolds (2001). The sample of 157 articles published in the Science Direct, Emerald, and Wiley databases was investigated. The period covers scientific literature published from 2001 to 2018. The paper shows the main theoretical concepts, methodological ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 108 publications
1
19
0
Order By: Relevance
“…A cut-off level of two was chosen, excluding any relationship that was not mentioned by at least two participants. The aim with the chosen cut-off level was to find a descriptive but not to complex value map [53]. Hierarchical value maps for groups of respondents that were considered to be relatively homogenous were constructed [46].…”
Section: Discussionmentioning
confidence: 99%
“…A cut-off level of two was chosen, excluding any relationship that was not mentioned by at least two participants. The aim with the chosen cut-off level was to find a descriptive but not to complex value map [53]. Hierarchical value maps for groups of respondents that were considered to be relatively homogenous were constructed [46].…”
Section: Discussionmentioning
confidence: 99%
“…Interviewees in this study consisted of 30 FB Live streaming shoppers in Thailand. The sample size of 20 to 25 people is recommended for this type of qualitative research and very few new insights are found beyond this point (Borgardt, 2020). To reach the interviewees, an advertisement was posted using FB ads which allowed FB users to sign up.…”
Section: Methodsmentioning
confidence: 99%
“…The software generated an implication matrix where each entry indicated the number of times an element was directly or indirectly mentioned by the interviewee to be related to another element. A cut-off point of 3 was used as recommended by prior research (Borgardt, 2020;Wagner, 2007). That is, the number of associations (N) must be mentioned at least three times to be considered relevant and such association would appear on the hierarchical value map (HVM).…”
Section: Methodsmentioning
confidence: 99%
“…, 2016). Borgardt (2020) reported that 52% of MEC studies used a soft laddering approach. Three interviewers were trained in MEC concepts and laddering techniques.…”
Section: Methodsmentioning
confidence: 99%
“…However, this method necessitates a highly skilled interviewer, is time-consuming, costly and is subject to interviewer bias (Arsil et al, 2016). Borgardt (2020) reported that 52% of MEC studies used a soft laddering approach. Three interviewers were trained in MEC concepts and laddering techniques.…”
Section: Samples and Proceduresmentioning
confidence: 99%